An acceptance of 4G (Fourth Generation) mobile network in Malaysia - Mat Sharif, Eizan Azira; Omar, Siti Zobidah (IRPN Press, 2013)
New technology makes possible for anyone and no doubt that the acceptance and usage of this interactive form of communication are auspicious. The launched of latest technology known as 4G in Malaysia provides the potential to change how a person works, live as well as communicates. The objectives of this paper are to assess the acceptance of 4G mobile network and to examine the factors that stimulate the usage of it. The researcher applied qualitative focus group and in-depth interview approach to collect data. A total of 15 informants is selected randomly. The findings indicated that the informants are contented and enthusiastic to use it in the future. The results from this research can be used to support as well as to develop upcoming 4G mobile network application. Further study concerning 4G mobile network is needed due to this technology is in its preliminary stage. The 4G mobile network seems to be a very promising invention of mobile communications and technology as it provides masses of interactive features and this may transform Malaysians’ life as well their acuities of the wireless communication epoch.